2022
DOI: 10.1016/j.renene.2021.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Fast torrefaction of large biomass particles by superheated steam: Enhanced solid products for multipurpose production

Abstract: Conventional torrefaction technology upgrade biomass for improved storage or as pretreatment prior to combustion or pyrolysis, and are generally performed on small-scale particles. Superheated steam (SHS) as the carrier gas and sole heat source was proposed to heat biomass rapidly and evenly while generating intensively torrefied biomass. This work revealed the potential of SHS torrefaction to upgrade large wood particles (F ¼ 30 mm, H ¼ 60 mm), to improve the feedstock suitability and expand products diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Numerous researches have been conducted in this area because of the significant interest in the growing field of torrefaction, which is predicted to become a major technology [10,11]. Studying the effect torrefaction of sugarcane bagasse on the ultimate, proximate and morphological properties at operating temperatures of 200-300 °C and 15--60-min retention duration showed that treated sugarcane bagasse had been sufficiently enhanced to be used in gasification process [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches have been conducted in this area because of the significant interest in the growing field of torrefaction, which is predicted to become a major technology [10,11]. Studying the effect torrefaction of sugarcane bagasse on the ultimate, proximate and morphological properties at operating temperatures of 200-300 °C and 15--60-min retention duration showed that treated sugarcane bagasse had been sufficiently enhanced to be used in gasification process [15].…”
Section: Introductionmentioning
confidence: 99%